Geometry nature of hydraulic fracture propagation from oriented perforations and implications for directional hydraulic fracturing. (September 2020) - Bai, Qingsheng; Liu, Zhenghe; Zhang, Cun; Wang, Fangtian
Abstract: In this study, hydromechanical hybrid finite-discrete element method (FDEM) models were employed to investigate hydraulic fracturing from oriented perforations at the microscale. Numerical calibrations were first used to obtain the microproperties that can represent the realistic behavior of sandstone. The fracture morphology and breakdown pressure obtained from the numerical hydraulic fracturing show reasonable agreements with the experimental results, indicating that the numerical results are convincing. Then, this method was applied to investigate the effects of the differential stress, perforation angle, perforation length, and injection rate on both the geometry nature of the hydraulic fractures (HFs) and the breakdown pressure. The perforation orientation, differential stress, and injection rate are found to strongly affect the breakdown pressure and HF geometry. However, the perforation length shows a weaker effect, especially when the perforation length is larger than the wellbore diameter. Furthermore, small-scale simulations were performed to investigate the formation of connected fractures developed from multiple perforated wellbores under the concept of directional hydraulic fracturing (DHF). The different fracture propagations and geometries in the DHF model indicate that conclusions from studying hydraulic fracturing from a single perforated wellbore may provide a limited reference for hydraulic fracturing from multiple perforated wellbores. The stress shadow effects during HF interactions were identified as the primary factor that contributed to these differences. Numerical results also provide new information on the roles of several factors (differential stress, injection rate, perforation orientation, and injection sequence) in DHF. DHF could take advantage of stress shadow effects by optimizing related factors. Based on the numerical results, some implications on the design of DHF, from small-scale simulations to field-scale applications, are discussed.